Public Perception of the Polri Superapp in Optimizing Public Services - Adnan Toyib; Cochi Suleijman Tangkudung; Estriastuti Nur Aisyah (Eduvest - Journal of Universal Studies, 2025)
Polri Super App is a digital innovation developed by the Indonesian National Police to enhance the efficiency and accessibility of public services. This study aims to analyze public perception of the Polri Super App in optimizing public services. The study employs a descriptive qualitative approach, with data collected through live and online interviews involving users of the application. The findings reveal that, while the Polri Super App is designed to simplify various administrative services—such as SIM renewal, SKCK applications, and police reports—many users still encounter significant challenges, including system malfunctions, registration errors, and limited public awareness or socialization. These issues contribute to low levels of user satisfaction and hinder the overall adoption of the application. The results highlight the need for technical improvements, better user interface design, and comprehensive public education to increase accessibility and trust in digital public services. The implications of this research underscore the importance of continuous evaluation and user-centered innovation in supporting the National Police’s efforts toward digital transformation and effective e-governance in Indonesia.